Evaluation of compressive strength, color stability, and antimicrobial action of chitosan-modified temporary crowns - Vatika Agarwal; Subhabrata Maiti; S Rajeshkumar; Sanjog Agarwal (Wolters Kluwer Medknow Publications, 2022)
This research was aimed at observing how antibacterial strength, colour stability, and compressive strength of chitosan modified PMMA compare to non modified PMMA [polymethyl methacrylate]. The study consisted of 2 groups - chitosan modified PMMA was the test group while unmodified PMMA was the control group. Twenty-four specimens were prepared for each group. Compressive strength was evaluated using the Universal testing machine. The antimicrobial action against streptococcus mutans and lactobacillus was evaluated using the disc diffusion method. A reflectance spectrophotometer was used to measure the baseline colour following the CIE L*a*b* scheme. Following these experiments, the specimens were submerged in coffee and distilled water solutions [n = 8] for 15 days each. Color stability was measured by comparing the coordinates obtained pre and post the ageing method. Independent t test used to examine data on colour change and compressive strength. [α = 0.05] It was observed that the incorporation of chitosan into polymethylmethacrylate increases its compressive strength. This was statistically significant [P = 0.00]. Improved colour stability was also observed [P = 0.000]. Antimicrobial action against streptococcus mutans and lactobacillus was seen in the chitosan modified group. Chitosan incorporation provides a promising improvement in the properties of the polymethylmethacrylate however further research with invivo studies are required to come to a conclusion.